Thought and exemplary Islamic nationalism of the early days of independence Indonesia: Learning from Ki Bagus Hadikusumo - Arif, Dikdik Baehaqi; Sapriya, Sapriya; Budimansyah, Dasim; Syaifullah, Syaifullah (Universitas Negeri Yogyakarta, 2025)
Indonesian nationalism is characterised by a blend of religious and national identities that coexist and reinforce each other. This paper presents a profile of the background of Ki Bagus Hadikusumo's thoughts, life, and nationalism during the early days of Indonesian independence. Ki Bagus Hadikusumo is one of Indonesia's national heroes who can be classified as an Islamic nationalist during the formulation of the Indonesian state. This figure, active in the Muhammadiyah Islamic movement organisation, has significantly contributed to the formulation and establishment of Pancasila as the basis of the state. The life background thought, and Muhammadiyah as the organisation of the Islamic movement have formed not only pure monotheistic attitudes and behaviours and precise tolerance but also a high sense of nationality and love for the homeland to provide exemplary social piety and statesmanship for citizens.